Project-Based Learning Model in Learning to Write Explanation Text for Vocational High School - Cahyono, Bambang Eko Hari; Widyaningrum, Heny Kusuma; Pratiwi, Cerianing Putri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
The purpose of this study is to describe and explain the ability to write explanatory texts of vocational school students, the implementation of the project-based learning (PjBL) model in improving the ability to write explanatory texts, and the strengths and weaknesses faced by teachers and students in implementing the project-based learning model. This research is crucial for enhancing the quality of writing instruction in vocational high schools. The research approach uses a qualitative descriptive approach. The subjects of this research were vocational high school students in Madiun. Data collection techniques were carried out through documentation, passive role observation, and) in-depth interviews. Data analysis was done using an interactive analysis model, carried out through 3 activity flows: data reduction, data presentation, and conclusion. This study revealed various problems in learning to write explanatory texts in vocational high schools. The results of the research show that: (1) students' ability to write explanatory texts is not by the structure of explanatory texts; (2) the direct impact of implementing the PjBL model is increasing students' ability to write explanatory texts; (3) the advantage of this model is that it provides experience for students that emphasizes practice in completing assignments and projects according to real-world conditions, while the disadvantages are that it requires the skills and activity of teachers and students, and quite time consuming especially in completing the project.